Mental health stigma and undergraduate nursing students: A self-determination theory perspective. Issue 2 (April 2020) - Perlman, Dana; Moxham, Lorna; Patterson, Christopher; Cregan, Anita; Alford, Stewart; Tapsell, Amy
Abstract: Background: Clinical placements are essential in preparing students for professional practice. Given the serious negative impact of stigma on people with lived experiences of mental illness, it is essential to explore whether the educational setting of a clinical placement can influence mental health stigma. Aims: Using a Self-Determination Theory lens, this study aimed to examine whether the educational setting of a clinical placemen influences the stigma of undergraduate nursing students toward people with lived experiences of mental illness. Design: Quasi-experimental; pre-test post-test. Methods: Ninety-nine undergraduate students enrolled in an accredited nursing program within Australia completed two surveys pre- and post-clinical placement. The surveys measured the educational setting (learning climate) and mental health stigma (social distance). Findings: Students who partook in an Autonomy-Supportive mental health clinical placement reported a significant decrease in stigma from pre-to-post placement, whereas the Balanced/Neutral group reported a significant increase in stigma from pre-to-post-placement. Discussion: The findings of this research have considerable implications for nursing facilitators and preceptors. Those that support autonomy amongst future nursing professionals are more likely to positively influence students' mental health stigma. Those who do not promote an autonomy-supportive setting may actually worsen mental health stigma. Conclusion: The educational setting in which a clinical placement occurs can influence nursing students' mental health stigma.